A transient photoactivation of epidermal stem cells by femtosecond laser promotes skin wound healing. Issue 12 (9th September 2022) - Hu, Bijin; Zhao, Xiaohui; Lu, Yiting; Zhu, Yujie; He, Hao
Abstract: Wound healing is a long‐term complex process, in which epidermal stem cells (EPSCs) in epidermis of skin have been found to play an essential role in it. We develop a noninvasive method to activate EPSCs in skin in vivo to promote wound healing, based on a microscopic system to enable a sequential frame‐by‐frame scanning of a femtosecond laser at 800 nm to the predefined skin region for a single time for 16 seconds. The laser is tightly focused on a submicron spot and localized in the epidermis, and scans point by point to activate EPSCs there. The density and stemness of EPSCs are significantly enhanced for at least 60 hours after the single‐time transient photoactivation. We demonstrate this method works in a skin wound mouse model. Our results provide an optical method for in vivo EPSC activation and hold good potential in wound healing. Abstract : Wound healing is a complex process in which epidermal stem cells (EPSCs) play an essential role. We develop a noninvasive method to activate EPSCs in skin in vivo to promote wound healing, based on a microscopic system to enable a sequential frame‐by‐frame scanning of a femtosecond laser at 800 nm to the predefined skin region for a single time for 16 seconds. We demonstrate this method in a skin wound mouse model. Our results provide an optical method for in vivo EPSC activation and hold good potential in wound healing.